Differences in Bullying Incidence Among Perpetrators and Victims Across Three Educational Levels: A Quantitative Comparative Study - Susi Muryani; Kamil Kustiarso; Theodora Rosaria (Universitas Muhammadiyah Semarang, 2026)
Bullying is a mental and social health problem that significantly affects the psychosocial development of children and adolescents. Differences in developmental characteristics across educational levels may influence individuals' involvement as perpetrators and victims. This study examines variations in bullying incidence from the viewpoints of both perpetrators and victims across three educational tiers (elementary, junior high, and senior high) in Tegal City, Indonesia. This quantitative study used a descriptive comparative design involving 90 students selected through purposive sampling (30 elementary, 30 juniors high, and 30 seniors high). Bullying perpetration and victimization were measured using the Peer Relations Questionnaire (PRQ). Data were analyzed using one-way ANOVA with a significance level of 0.05. There was a significant difference in bullying victim scores across educational levels (F=3.935, p=0.023), with higher victimization among junior high (mean=9.07) and senior high students (mean=8.87) compared to elementary students (mean=7.37). Perpetrator scores showed variation between levels (elementary mean=7.87, junior high mean=8.67, and senior high mean=8.83), but differences did not reach strong statistical significance. These findings support Erikson's psychosocial developmental theory that adolescents in the identity versus role confusion stage are more vulnerable to relational conflict and social pressure, increasing victimization risk. Bullying incidence, particularly from the victim perspective, differs significantly across educational levels, indicating the need for developmentally tailored prevention strategies in schools.